Garden of beasts : a novel of Berlin 1936 - Deaver, Jeffery (Pocket Books, 2022)
"Paul Schumann, a German American living in New York City in 1936, is a mobster hit man known as much for his brilliant tactics as for taking only "righteous" assignments. But then Paul gets caught. And the arresting officer offers him a stark choice: execution or covert government service. Paul is asked to pose as a journalist covering the summer Olympics taking place in Berlin. He's to hunt down and kill Reinhard Ernst--the ruthless architect of Hitler's clandestine rearmament. If successful, Paul will be pardoned and given the financial means to go legit. Paul travels to Germany, takes a room in a boardinghouse near the Tiergarten--the huge park in central Berlin but also, literally, the "Garden of Beasts"--and begins his hunt. Garden of Beasts, which won the Steel Dagger Award from the Crime writers' Assoiationin the UK, is packed with fascinating period detail and features a cast of perfectly realized locals, Olympic athletes and senior Nazi officials--some real, some fictional. With hairpin plot twists, the reigning "master of ticking-bomb suspense" (People) plumbs the nerve-jangling paranoia of prewar Berlin and steers the story to a breathtaking and wholly unpredictable ending."--